2005
DOI: 10.1007/s00415-005-0839-3
|View full text |Cite
|
Sign up to set email alerts
|

Severe delayed heart failure in three multiple sclerosis patients previously treated with mitoxantrone

Abstract: Mitoxantrone is an approved drug for patients with worsening relapsing-remitting, secondary progressive and progressive relapsing multiple sclerosis (MS). From a cohort of 820 MS patients, 52 (6%) were treated with this drug between December 1991 and April 2003. Mitoxantrone was administered at a dose of 12 mg/m(2) once a month for three months and then at three-month intervals to reach a total cumulative dose of 144 mg/m(2). The left ventricular ejection fraction was checked by radionuclide ventriculography p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 27 publications
0
28
0
2
Order By: Relevance
“…12 One Class III study of 96 patients who received a cumulative dose of 48 mg/m 2 of MX over 1 year reported asymptomatic decreased LVEF in 6 patients. 13 Three of these patients had LVEF Ͻ50% at 6 months and discontinued therapy.…”
mentioning
confidence: 99%
“…12 One Class III study of 96 patients who received a cumulative dose of 48 mg/m 2 of MX over 1 year reported asymptomatic decreased LVEF in 6 patients. 13 Three of these patients had LVEF Ͻ50% at 6 months and discontinued therapy.…”
mentioning
confidence: 99%
“…This would also justify the observed higher proportion of heart events in our cohort although the reported risk is not significant, probably because of the low number of events. Other explanations for differences in observed results may depend on the criteria and methodology used in other studies to define and to assess the presence and the severity of heart diseases [10,11]. As already mentioned, the distribution of clinical phenotypes of MS patients included in the study, as well as age at initiation of MTX therapy, have to be considered possible factors determining a modification of the observed effects when comparing present results with those from other studies [12].…”
Section: Discussionmentioning
confidence: 85%
“…Fewer data are available on long-term cardiac effects of MTX treatment. Goffette et al [10] described 3 patients in whom congestive HF developed at 24, 29, and 60 months after administration of the last MTX dose. Two of these patients were previously treated with cyclophosphamide which might have increased the cardiotoxic effect of MTX [10].…”
Section: Discussionmentioning
confidence: 99%
“…Goffette et al [10] described 3 patients in whom congestive HF developed at 24, 29, and 60 months after administration of the last MTX dose. Two of these patients were previously treated with cyclophosphamide which might have increased the cardiotoxic effect of MTX [10]. During 3 years of follow-up, Hartung et al [8] reported 4 cases of asymptomatic LVEF reduction in a group of 196 patients, with no case of congestive HF resulting from MTX treatment [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation